A knowledge-based retrofit priority identification framework of the mineral processing to assist in process improvement - Furong Sun; Dakuo He; Hongying Lin; Qiang Li; Chun Wang; Jiacheng Liu; Duanduan Wang (Minerals Engineering, 2026)

First record of Brachyphyllum (Cheirolepidiaceae) from the Lower Jurassic of the Ordos Basin, China: Paleogeographic and paleoclimatic implications linked to T-OAE - Chao-Hui Wei; Yun-Feng Li; Chang-Lu Zhang; Xiao Tan; Fei Liang; Chun-Lin Sun; Tao Li; Yu-Ling Na (Review of Palaeobotany and Palynology, 2026)

Experimental and numerical study of diaphragm in-plane stiffness on the seismic performance of building structures with DCPCF - Yuan-yuan Sun; Rui Pang; Shu-ting Liang; Yi-ming Wen; Chun-lin Wang (Engineering Structures, 2026)

Full mechanical response prediction for staged prestressed composite beams driven by a hybrid GRU-VAE and BiLSTM framework - Zexuan Sun; Tianxia Cui; Man Xu; Bin Zeng; Chun-Lin Wang (Engineering Structures, 2026)

An immersed boundary-recursive regularized lattice Boltzmann method for flow-induced noise prediction with moving bodies - Lei Jin; Guang-yu Shi; Chun-yu Guo; Lin Cai; Lu-cheng Sun; Yuan-jian Yao (Ocean Engineering, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Host-derived Bacillus velezensis enhances intestinal structure, antioxidant capacity, and pathogen resistance in the American bullfrog (Aquarana catesbeiana) - Yueming Hu; Han Lin; Mengzhen Jiang; Changyi Lin; Hua Li; Jingyang Sun; Kesong Chen; Yebing Yu; Chun Liu (Archives of Microbiology, 2026)

Boosting char formation in lignin aerogels via PN synergy: A route to flame retardancy and multifunctional performance - Jia-Hui Wang; Tao Gui; Shuang-Lin Zou; Qing-Hua Wang; Ying-Chun Xu; Rong Tan; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Chemical Engineering Journal, 2026)

Neutrophil extracellular traps in post-traumatic urethral microenvironment promote hypertrophic urethral stricture via the TLR9/NF-kB/Smad3/IL-8 axis - Ye-Hui Chen; Zhi-Bin Ke; Bo-Han Lin; Yi-Cheng Xu; Xue-Yi Xue; Qing-Shui Zheng; Xiong-Lin Sun; Yong Wei; Ying-Chun Liang; Ning Xu (Apoptosis, 2026)

Catalase is a critical virulence factor in Aeromonas schubertii infection of snakehead fish (Channa argus) - Mengzhen Jiang; Haiyan Gong; Qing Wang; Han Lin; Yueming Hu; Hua Li; Jingyang Sun; Kesong Chen; Biao Jiang; Wei Li; Youlu Su; Chun Liu (Antonie van Leeuwenhoek, 2026)

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

16S rDNA sequencing combined with non-targeted metabolomics profiling reveals the mechanism of simulated digestion ultra-sound pea protein isolate in vitro - Xinyu Zhao; Xuemei Dong; Jianke Fang; Chun Li; Lin Zhao; Guofang Zhang; Peng Du; Tong Zhang; Xinyao Sun; Libo Liu; Wenkui Guo (Food Bioscience, 2026)

Unraveling iron and zinc efficiency in pepper: integration of root architecture, uptake kinetics, and transcriptional regulation - Cheng-Xiang Zhou; Wei Zhang; Bao-Gang Yu; Hao-Feng Yang; Yuan Wang; Kai Sun; Fu-Lin Zhao; Huai-Yu Yang; Prakash Lakshmanan; Xin-Ping Chen; Chun-Qin Zou (Plant and Soil, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Mechanisms of cell death in Klebsiella pneumoniae-induced acute splenic injury in Aquarana catesbeiana - Han Lin; Hua Li; Kesong Chen; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Qing Wang; Youlu Su; Li Lin; Chun Liu (Aquaculture, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Advanced functionalization strategies of chitin and chitosan toward sustainable nanocomposites - Shuang-Lin Zou; Xin-Ran Liu; Jia-Hui Zhang; Ying-Chun Xu; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Carbohydrate Polymers, 2026)

Life cycle assessment of a food waste-based biorefinery: From production of biopolymers to fabrication of advanced nanofibre masks - Jia-Le Zhu; Zi-Hao Qin; Johnny Sik Chun Lo; Zhen-Yao Wang; Jin-Hua Mou; Anda Fridrihsone; Zheng Sun; Carol Sze Ki Lin (Journal of Cleaner Production, 2026)

The effects of active surface morphing on the propulsive performance and acoustic characteristics of a flapping foil - Chun-yu Guo; Lei Jin; Guang-yu Shi; Lin Cai; Lu-cheng Sun; Yi-jie Sun (Ocean Engineering, 2025)

Experimental and analytical investigations on the bearing capacity of staged prestressed composite beams - Zexuan Sun; Yong Zhao; Tianxia Cui; Bin Zeng; Chun-Lin Wang (Engineering Structures, 2025)

Charcoal-derived hard carbon anodes with enhanced sodium storage performance for sodium-ion batteries - Shengchen Yang; Yan Li; Chun Chen; Hui Wang; Kaihang Wang; Qingqing Li; Ruize Dong; Manman Chen; Cai Zhao; Weiwei Xu; Lin Sun; Tao Zhang; et al. (Chemical Engineering Journal, 2025)

Covalent organic frameworks with synergistic linkages and functional groups boost electrochemiluminescence for sensitive detection of long non-coding RNA - Linlin Song; Lin Cui; Xiaoran Zou; Xueting Cao; Wenqi Chu; Wenjie Gao; Lin Cheng; Bing Sun; Chun-yang Zhang (Chemical Engineering Journal, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Adaptive fertilization strategies for premature senescence challenges in film-mulched maize: Insights from a 4-year field study - Haixiang Xiong; Chi Ma; Shujie Sun; Ziyi Wang; Ji Zhao; Chun Zhang; Lin Yang; Zhaoyun Dong; Zhikuan Jia; Dan Liu; Qingfang Han; Xudong Zhang (European Journal of Agronomy, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

A portable point-of-care testing platform for rapid and sensitive miRNA-21 detection for heart failure diagnosis - Qian Kai Lin; Wen Qing Sun; Bo Zhang; Qiao Ling; Yan Qian; Cheng Zhi Huang; Chun Mei Li; Na Wang (Analytica Chimica Acta, 2025)

Frog virus 3: Prevalence survey and quantitative analysis in American bullfrogs using TaqMan MGB probe real-time fluorescence quantitative PCR - Hua Li; Xiaobing Liu; Jingyang Sun; Han Lin; Kesong Chen; Yueming Hu; Mengzhen Jiang; Biao Jiang; Wei Li; Youlu Su; Qing Wang; Chun Liu (Aquaculture, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

In search of nanofiltration membranes for efficient lithium extraction from carbonate-type salt lakes - Ren-Jie Fan; Chun-Xu Zhang; Fujun Xiong; Lin-Hui Niu; Xiang-Xuan Ruan; Xiaohu Wang; Zhen-Yuan Wang; Mei-Ling Liu; Shi-Peng Sun; Weihong Xing (Desalination, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Numerical study of relationships between flows and structural characteristics of the rotor in a rim-driven hubless thruster using a strongly-coupling FSI algorithm - Chun Yang; Hua-Dong Yao; Cong Sun; Chao Wang; Chunyu Guo; Jianfeng Lin (Ocean Engineering, 2025)

Enhanced virulence of Acinetobacter johnsonii at low temperatures induces acute immune response and systemic infection in American bullfrogs (Aquarana catesbeiana) - Han Lin; Jingyang Sun; Hua Li; Kesong Chen; Zhendong Qin; Biao Jiang; Wei Li; Qing Wang; Youlu Su; Li Lin; Chun Liu (Veterinary Microbiology, 2025)

The overlooked shadow killer: Elizabethkingia anophelis as a potent pathogen in American bullfrogs (Aquarana catesbeiana) - Chun Liu; Han Lin; Jie Ma; Yebing Yu; Ruinan Wang; Xinyi Tang; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin (Aquaculture, 2025)

Sesquiterpenoids from the whole plants of Elephantopus mollis with cytotoxicity activities - Qiang Lin; Jing-Yi Du; Si-Yu Yang; Zhao-Chun Zhan; Qing Tang; Hui Sun; Jin-Lin Tan; Hai-Yue Zhao; Yao-Lan Li; Yu-Bo Zhang; Guo-Cai Wang (Natural Product Research, 2025)

Surface chemistry regulation enables highly durable superhydrophobic coatings with environmental robustness and pH-triggered recoatability - Mei-Lin Guo; Fang Wang; Ren-Yi Sun; Chun-Bo Li; Jin-Le Li; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

An innovative enhanced flotation approach of non-metallic components in waste printed circuit boards: Application of pyrolysis oil as self-generated collector - Chun-chen Nie; Qian-yun Sun; Xi-guang Li; Shuo Yang; Fei-fei Wang; Gang Hu; Si-qi Jiang; Xiang-nan Zhu; Lin Li; Xiao-fang You (Process Safety and Environmental Protection, 2024)

A high-entropy strategy for stable structure of sodium ion batteries: From fundamentals to applications - Xu Liu; Xin-Yu Liu; Nan Zhang; Peng-Fei Wang; Zong-Lin Liu; Jun-Hong Zhang; Jie Shu; Yan Sun; Chun-Sheng Li; Ting-Feng Yi (Chemical Engineering Journal, 2024)

Genomic analysis of Alteromonas sp. M12 isolated from the Mariana Trench reveals its role in dimethylsulfoniopropionate cycling - Yue Lin; Min Zhang; Yu-Xiang Lai; Teng Liu; Meng Meng; Yan Sun; Yu Wang; Qing-Yu Dong; Chen-Xi Li; Meng-Xue Yu; Jin Cheng; Shu-Jun Liu; et al. (Marine Genomics, 2024)

Clean and efficient process for the recycling of all components from waste printed circuit boards: Pre-treatment, bio-metallurgy, and deep utilization - Chun-chen Nie; Xi-guang Li; Qian-yun Sun; Qiang Gao; Xiang-nan Zhu; Xian-jun Lyu; Lin Li; Xiao-fang You (Journal of Cleaner Production, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

Deformation characteristics and stability analysis of lean clay under cyclic loading - Han-Lin Wang; Yue-Hui Sun; Ren-Peng Chen; Chun-Yin Peng; Askar Khasanov (Transportation Geotechnics, 2024)

Phellintremulins A-C, antinociceptive sesquiterpenoids from the medicinal fungus Phellinus tremulae - Chun Tian; Li-Tang Sun; Tian Jin; Lin-Lin Yuan; Wei-Fang Xu; Hui-Xiang Yang; Tao Feng; Ji-Kai Liu (Phytochemistry, 2024)

Nitrogen fertilization modulates rice phyllosphere functional genes and pathogens through fungal communities - Wei-Feng Wu; Xin-Yuan Li; Song-Can Chen; Bing-Jie Jin; Chun-Yan Wu; Gang Li; Cheng-liang Sun; Yong-Guan Zhu; Xian-Yong Lin (Science of The Total Environment, 2024)

Long-term PM1 exposure and hypertension hospitalization: A causal inference study on a large community-based cohort in South China - Yuqin Zhang; Shirui Chen; Jing Wei; Jie Jiang; Xiao Lin; Ying Wang; Chun Hao; Wenjing Wu; Zhupei Yuan; Jie Sun; Han Wang; Zhicheng Du; et al. (Science Bulletin, 2024)

A top-down and in situ strategy for intrinsic acicular nanostructure enhanced ultradurable superhydrophobic and anti-icing aramid fabric - Jin-Le Li; Fang Wang; Chun-Bo Li; Ren-Yi Sun; Mei-Lin Guo; Gang Wu; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Low temperature promotes the production and efflux of terpenoids in yeast - Lei Qin; Dongshi Ma; Guangyuan Lin; Wentao Sun; Chun Li (Bioresource Technology, 2024)

Cellular localization and potential ligands of a novel scavenger receptor class B/CD36 protein homolog (Pt-SRB2) identified in the marine crab, Portunus trituberculatus - Su-Ming Zhou; Fang-Mei Lin; Chang-Kao Mu; Chun-Lin Wang; Qi-Cun Zhou; Peng Sun; Fei Yin (Fish & Shellfish Immunology, 2024)

Ubiquitination-specific protease 7 enhances stemness of hepatocellular carcinoma by stabilizing basic transcription factor 3 - Mingchao Hu; Chengchen Dai; Xieyin Sun; Yinqi Chen; Nuo Xu; Zhaoyi Lin; Shiyu Xu; Chun Cheng; Zhonghua Tan; Saiyan Bian; Wenjie Zheng (Functional & Integrative Genomics, 2024)

Wide-swath and high-resolution whisk-broom imaging and on-orbit performance of SDGSAT-1 thermal infrared spectrometer - Zhuoyue Hu; Xiaoyan Li; Liyuan Li; Xiaofeng Su; Lin Yang; Yong Zhang; Xingjian Hu; Chun Lin; Yujun Tang; Jian Hao; Xiaojin Sun; Fansheng Chen (Remote Sensing of Environment, 2024)

Induced differentiation of primordial germ cell like cells from SOX9+ porcine skin derived stem cells - Geng Zhang; Xin-Xiang Xie; Shu-Er Zhang; Fa-Li Zhang; Chun-Xiao Li; Tian Qiao; Paul W. Dyce; Xin-Lei Feng; Wei-Bo Lin; Qi-Cheng Sun; Wei Shen; Shun-Feng Cheng (Theriogenology, 2023)

Dual-channel MIRECL portable devices with impedance effect coupled smartphone and machine learning system for tyramine identification and quantification - Zhiwei Lu; Jun Qin; Chun Wu; Jiajian Yin; Mengmeng Sun; Gehong Su; Xianxing Wang; Yanying Wang; Jianshan Ye; Tao Liu; Hanbing Rao; Lin Feng (Food Chemistry, 2023)

An accurate and efficient HOS-meshfree CFD coupling method for simulating strong nonlinear wave–body interactions - Chun-Mei Xie; Jun-Cheng Yang; Peng-Nan Sun; Hong-Guan Lyu; Jun Yu; Yong-Lin Ye (Ocean Engineering, 2023)

Oxygen doped graphite carbon nitride as efficient metal-free catalyst for peroxymonosulfate activation: Performance, mechanism and theoretical calculation - Shaofeng Xiang; Yu Lin; Tongda Chang; Bingrui Mei; Yuhang Liang; Ziqian Wang; Wenwu Sun; Chun Cai (Chemosphere, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Dating seafloor spreading of the southwest sub-basin in the South China Sea - Ning Qiu; Zhen Sun; Jian Lin; Chun-Feng Li; Xing Xu (Gondwana Research, 2023)

Detection and quantification of Klebsiella pneumoniae in American bullfrog (Rana catesbeiana) by Taqman MGB probe real-time fluorescence quantitative PCR - Han Lin; Jingyang Sun; Jie Ma; Zhendong Qin; Biao Jiang; Wei Li; Qing Wang; Youlu Su; Li Lin; Chun Liu (Aquaculture, 2023)

Residue screening and analysis of enrofloxacin and its metabolites in real aquatic products based on ultrahigh-performance liquid chromatography coupled with high resolution mass spectrometry - Jinxia Dai; Ye Wang; Hui Lin; Yanmin Sun; Yuning Pan; Jun-qin Qiao; Hong-zhen Lian; Chun-xiang Xu (Food Chemistry, 2023)

Determination of chlorpromazine and its metabolites in animal-derived foods using QuEChERS-based extraction, EMR-Lipid cleanup, and UHPLC-Q-Orbitrap MS analysis - Jinxia Dai; Hui Lin; Yuning Pan; Yanmin Sun; Ye Wang; Jun-qin Qiao; Hong-zhen Lian; Chun-xiang Xu (Food Chemistry, 2023)

Spinal P2X4 Receptors Involved in Visceral Hypersensitivity of Neonatal Maternal Separation Rats - Ying Tang; Li Chen; Bin Liu; Pei Sun; Zhong Chen; Yang Huang; Chen Ai-qin; Yu Chen; Chun Lin (Purinergic Signalling, 2023)

Establishing a high-performance anti-fouling PEI-ZIF-PAA membrane with improved Lewis acid-base interactions and hydrophilicity - Zhang-Hong Wan; Jing Guan; Chun-Miao Zhang; Wen-Qing Fei; Lin Wang; Shu-Guang Wang; Xue-Fei Sun (Chemosphere, 2023)

NRP1 contributes to stemness and potentiates radioresistance via WTAP-mediated m6A methylation of Bcl-2 mRNA in breast cancer - Yang Wang; Lin Zhang; Xiao-Lin Sun; Ya-Chun Lu; Si Chen; Dong-Sheng Pei; Lan-Sheng Zhang (Apoptosis, 2023)

Impacts of hydraulic conditions on microplastics biofilm development, shear stresses distribution, and microbial community structures in drinking water distribution pipes - Xiao Chen; Xiao-ying Lian; Yi Wang; Sheng Chen; Yi-ran Sun; Guo-lin Tao; Qiao-wen Tan; Jing-chun Feng (Journal of Environmental Management, 2023)

The therapeutic potential of diet on immune-related diseases: based on the regulation on tryptophan metabolism - Junjie Lin; Dongxiao Sun-Waterhouse; Chun Cui (Critical Reviews in Food Science and Nutrition, 2022)

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

Polyethylene microplastic exposure and concurrent effect with Aeromonas hydrophila infection on zebrafish - Ning Ding; Lin Jiang; Xiao Wang; Chun Wang; Yue Geng; Jianxin Zhang; Yingxue Sun; Yanping Zhang; Quan Yuan; Hong Liu (Environmental Science and Pollution Research, 2022)

Plant secondary metabolite and temperature determine the prevalence of Arsenophonus endosymbionts in aphid populations - Chun‐Yan Chang; Xiao‐Wan Sun; Pan‐Pan Tian; Ning‐Hui Miao; Yu‐Lin Zhang; Xiang‐Dong Liu (Environmental Microbiology, 2022)
Summary Transmission rate and role in hosts contribute to the prevalence of an endosymbiont. However, factors affecting transmission and role of facultative endosymbionts are still not well understood. Here, we illustrated that host plants and environmental temperatures affected the transmission, relative abundance and role of Arsenophonus in the cotton aphid Aphis gossypii . The transmission rate of this endosymbiont from mother aphids to offspring was relatively lower. High temperatures impeded the transmission, and infection rates declined as aphids were exposed to 30°C. Contents of amino acids and secondary metabolites were remarkably different among host plants. Aphids feeding on zucchini leaves containing a higher titre of amino acids and lower secondary metabolites harboured a relatively lower abundance of Arsenophonus . Concentrations of an amino acid and a plant secondary metabolite, cucurbitacin B, in aphid diet were not associated with Arsenophonus abundance. However, gossypol, another plant secondary metabolite, was strongly related with the abundance. Arsenophonus imparted a fitness benefit to aphids, and the benefit was dependent on host plants and gossypol concentration. In sum, plant secondary metabolite and environmental temperature affect transmission, relative abundance and role of Arsenophonus , which determine the endosymbiont prevalence in aphid populations.

Halomonas populi sp. nov. isolated from Populus euphratica - Lin Xu; Jun-Jie Ying; Yuan-Chun Fang; Ran Zhang; Jia Hua; Min Wu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2022)

Marinomonas vulgaris sp. nov., a marine bacterium isolated from seawater in a coastal intertidal zone of Zhoushan island - Jun-Jie Ying; Yuan-Chun Fang; Yong-Lian Ye; Zhi-Cheng Wu; Lin Xu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Engrafted primary type-2 astrocytes improve the recovery of the nigrostriatal pathway in a rat model of Parkinson's disease - Yanyun Sun; Xiao-jun Lu; Xinghui Fu; Ye Zhang; Yan Zhan; Jiabing Liu; Lingxia Zhao; Chun-lin Xia (Molecular and Cellular Biochemistry, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Infusion of Human Mesenchymal Stem Cells Improves Regenerative Niche in Thioacetamide-Injured Mouse Liver - Ying-Hsien Kao; Yu-Chun Lin; Po-Huang Lee; Chia-Wei Lin; Po-Han Chen; Tzong-Shyuan Tai; Yo-Chen Chang; Ming-Huei Chou; Chih-Yang Chang; Cheuk-Kwan Sun (Tissue Engineering and Regenerative Medicine, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

Ancestral niche separation and evolutionary rate differentiation between sister marine flavobacteria lineages - Chun‐Xu Xue; Hao Zhang; He‐Yu Lin; Ying Sun; Danli Luo; Yongjie Huang; Xiao‐Hua Zhang; Haiwei Luo (Environmental Microbiology, 2020)
Summary Marine flavobacteria are specialists for polysaccharide degradation. They dominate in habitats enriched with polysaccharides, but are also prevalent in pelagic environments where polysaccharides are less available. These niches are likely occupied by distinct lineages, but evolutionary processes underlying their niche differentiation remain elusive. Here, genomic analyses and physiological assays indicate that the sister flavobacteria lineages Leeuwenhoekiella and Nonlabens likely explore polysaccharide‐rich macroalgae and polysaccharide‐poor pelagic niches respectively. Phylogenomic analyses inferred that the niche separation likely occurred anciently and coincided with increased sequence evolutionary rate in Nonlabens compared with Leeuwenhoekiella . Further analyses ruled out the known mechanisms likely driving evolutionary rate acceleration, including reduced selection efficiency, decreased generation time and increased mutation rate. In particular, the mutation rates were determined using an unbiased experimental method, which measures the present‐day populations and may not reflect ancestral populations. These data collectively lead to a new hypothesis that an ancestral and transient mutation rate increase resulted in evolutionary rate increase in Nonlabens . This hypothesis was supported by inferring that gains and losses of genes involved in SOS response, a mechanism known to drive transiently increased mutation rate, coincided with evolutionary rate acceleration. Our analyses highlight the evolutionary mechanisms underlying niche differentiation of flavobacteria lineages.

Potential role of IL-37 signaling pathway in feedback regulation of autoimmune Hashimoto thyroiditis - Cui-Ping Ren; Li Sun; Feng-Chun Liu; Chun-Lin Zuo; Miao Liu; Wenda Gao; Ji-Jia Shen (Histochemistry and Cell Biology, 2019)

Development of Multi-axis Motor Control Systems for Lower Limb Robotic Exoskeleton - Cheng-Tang Pan; Chun-Chieh Chang; Pei-Yuan Sun; Cheng-Lung Lee; Tzu-Chieh Lin; Chung-Kun Yen; Yu-Sheng Yang (Journal of Medical and Biological Engineering, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Dose Verification for Tumor Motion with Different Treatment Planning Systems: A Dynamic Thorax Phantom Study - Shih-Neng Yang; Chun-Wei Lin; Mu-Bai Chang; Geoffrey G. Zhang; Kuei-Ting Chou; Yu-Rou Chiou; Shung-Shung Sun; Louis Lui; Tsung-Jung Ho; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

The complete mitochondrial genome of Budorcas taxicolor bedfordi (Artiodactyla: Bovidae) and phylogenetic studies of Caprinae - Mao-hong Sun; Chun-wang Yue; Ting-ting Liu; Lin Li; Hai-ying Liu (Conservation Genetics Resources, 2017)

Effects of temperature, salinity, diet and stocking density on development of the veined Rapa whelk, Rapana venosa (Valenciennes, 1846) larvae - Tao Zhang; Hao Song; Yu-Cen Bai; Jing-Chun Sun; Xiao-Fang Zhang; Shao-Jun Ban; Zheng-Lin Yu; Mei-Jie Yang; Hai-Yan Wang (Aquaculture International, 2017)

Effect of climate change on seasonal water use efficiency in subalpine Abies fabri - Xiang-yang Sun; Gen-xu Wang; Mei Huang; Zhao-yong Hu; Chun-lin Song (Journal of Mountain Science, 2017)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

A new phenylethanoid glycoside from Orobanche cernua Loefling - Zheng-yi Qu; Yu-wei Zhang; Si-wen Zheng; Chun-lin Yao; Yin-ping Jin; Pei-he Zheng; Cheng-he Sun; Ying-ping Wang (Natural Product Research, 2016)

Oxidation of aniline aerofloat in flotation wastewater by sodium hypochlorite solution - Weixiong Lin; Jing Tian; Jie Ren; Pingting Xu; Yongkang Dai; Shuiyu Sun; Chun Wu (Environmental Science and Pollution Research, 2016)

Diversity and space–time dynamics of endophytic archaea from sugar beet in the north slope of Tianshan Mountain revealed by 454 pyrosequencing and T-RFLP - YingWu Shi; MuSi TaPa; Chun Li; HongMei Yang; Tao Zhang; Yan Gao; Jian Sun; Jun Zeng; Qing Lin; ZhenHua Cao; KuEr OuTi; YuGuo Li; et al. (World Journal of Microbiology and Biotechnology, 2015)

A large-scale breeding experiment and observations on development of Cyanea nozakii (Scyphozoa, Cyaneidae) from fertilized eggs to larval medusae - Chun-sheng Liu; Zhi-meng Zhuang; Si-qing Chen; Jing-ping Yan; Chang-lin Liu; Jian-ming Sun (Hydrobiologia, 2015)

The differential roles of Slit2-exon 15 splicing variants in angiogenesis and HUVEC permeability - Yun-Chiu Yang; Pei-Ni Chen; Siou-Yu Wang; Chen-Yi Liao; Yu-Ying Lin; Shih-Rhong Sun; Chun-Ling Chiu; Yih-Shou Hsieh; Jia-Ching Shieh; Jinghua Tsai Chang (Angiogenesis, 2015)

Erratum to: Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Production and Characteristics of High Quality Vinegar from Sugarcane Juice - Gan-Lin Chen; Feng-Jin Zheng; Jian Sun; Zhi-Chun Li; Bo Lin; Yang-Rui Li (Sugar Tech, 2015)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

The cellular community in the intestine of the shrimp Penaeus penicillatus and its culture environments - Chun-zhong Wang; Guo-rong Lin; Tao Yan; Zhi-peng Zheng; Bin Chen; Fu-lin Sun (Fisheries Science, 2014)

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2014)

New Evidence for the Role of Ethylene in Strawberry Fruit Ripening - Jing-Hua Sun; Jing-Jing Luo; Lin Tian; Chun-Li Li; Yu Xing; Yuan-Yue Shen (Journal of Plant Growth Regulation, 2013)

Adhesion of osteoblast-like cell on silicon-doped TiO2 film prepared by cathodic arc deposition - Bing Wang; Jun-Ying Sun; Shi Qian; Xuan-Yong Liu; Shai-Lin Zhang; Sheng-Jie Dong; Guo-Chun Zha (Biotechnology Letters, 2013)

Impact of manure application on forms and quantities of phosphorus in a Chinese Cambisol under different land use - Qiao Yun Xue; Imran Haider Shamsi; Da Sheng Sun; Anne Ostermann; Qi Chun Zhang; Yong Song Zhang; Xian Yong Lin (Journal of Soils and Sediments, 2013)

A study of the frequency of methylation of gene promoter regions in colorectal cancer in the Taiwanese population - CHANG-CHIEH WU; JEN-CHUN KUAN; CHIH-HSIUNG HSU; TZU-AN CHEN; CHIEN-AN SUN; TSAN YANG; SHINN-LONG LIN; YU-CHING CHOU (Journal of Genetics, 2013)

Does glyphosate impact on Cu uptake by, and toxicity to, the earthworm Eisenia fetida? - Chui-Fan Zhou; Yu-Jun Wang; Yuan-Chun Yu; Rui-Juan Sun; Xiang-Dong Zhu; Hai-Lin Zhang; Dong-Mei Zhou (Ecotoxicology, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

The dissection and SSR mapping of a high-temperature adult-plant stripe rust resistance gene in American spring wheat cultivar Alturas - Lei Zhao; Jing Feng; Chun-Yu Zhang; Xiao-Dan Xu; Xian-Ming Chen; Quan Sun; Qing Miao; Shi-Chang Xu; Feng Lin (European Journal of Plant Pathology, 2012)

Juglanthraquinone C, a novel natural compound derived from Juglans mandshurica Maxim, induces S phase arrest and apoptosis in HepG2 cells - Yao Yao; Yu-Wei Zhang; Lu-Guo Sun; Biao Liu; Yong-Li Bao; Hua Lin; Yu Zhang; Li-Hua Zheng; Ying Sun; Chun-Lei Yu; Yin Wu; Guan-Nan Wang; et al. (Apoptosis, 2012)

Analysis of Isocitrate Dehydrogenase 1 Mutation in 97 Patients with Glioma - You-Xin Zhou; Jun-Xiang Wang; Ming Feng; Chun-Ming Sun; Ting Sun; Gui-Lin Chen; Zi-Wei Du (Journal of Molecular Neuroscience, 2012)

Donor-Acceptor Compound Based on Rhodanineacetic Acid-Pyrene Derivative: Red-Light Emitting Fluorescent Organic Nanoparticles - Bo Zhang; Wei Diao; Chun Bi; Jian Sun; Guoxia Han; Yi Shi; Li Sheng; Gui Yin; Lin Pu (Journal of Fluorescence, 2012)

Evaluation of Left Ventricular Twist in Acute Myocardial Infarction Patients Using Speckle Tracking Imaging - Da-lin Jia; Chun-yan Ma; Shuang Liu; Lu-fan Sun (Cell Biochemistry and Biophysics, 2011)

How to amend land subsidence treatment policies to solve coastal subsidence problems in Taiwan - Peter Lin Sun; Chun-Chou Yang; Tai-Wai Lin (Regional Environmental Change, 2011)

Interspecific hybrids between Chrysanthemum grandiflorum (Ramat.) Kitamura and C. indicum (L.) Des Moul. and their drought tolerance evaluation - Chun-Qing Sun; Fa-Di Chen; Nian-Jun Teng; Zhao-Lei Liu; Wei-Min Fang; Xi-Lin Hou (Euphytica, 2010)

3D Micro-Crack Propagation Simulation at Enamel/Adhesive Interface Using FE Submodeling and Element Death Techniques - Heng-Liang Liu; Chun-Li Lin; Ming-Tsung Sun; Yen-Hsiang Chang (Annals of Biomedical Engineering, 2010)

Factors affecting seed set in the crosses between Dendranthema grandiflorum (Ramat.) Kitamura and its wild species - Chun-Qing Sun; Fa-Di Chen; Nian-Jun Teng; Zhao-Lei Liu; Wei-Min Fang; Xi-Lin Hou (Euphytica, 2010)

Changes in estrogen receptor-α variant (ER-α36) expression during mouse ovary development and oocyte meiotic maturation - Bao-Zeng Xu; Sheng-Li Lin; Mo Li; Jia-Qiao Zhu; Sen Li; Ying-Chun Ouyang; Da-Yuan Chen; Qing-Yuan Sun (Histochemistry and Cell Biology, 2009)

Changes of Src-suppressed C kinase substrate expression in cytokine induced reactive C6 glioma cells - Lin-Lin Sun; Chun Cheng; Hai-Ou Liu; Feng Xiao; Jing Qin; Xiao-Yi Shao; Ai-Guo Shen (Neuroscience Bulletin, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Identification ofporphyra lines (rhodophyta) by AFLP DNA fingerprinting and molecular markers - Jian Wei Sun; Min De Jin; Chun Jiang Zhou; Qing Kai Yang; Man Li Weng; Lin De Duan; Pu Xu; Jia Hai Ma; Bin Wang (Plant Molecular Biology Reporter, 2005)

Estradiol, aromatase and steroid receptors involved in the sex change of protandrous black porgy, Acanthopagrus schlegeli - Jin-Lien Du; Bih-Yun Lin; Yan-Hoarn Lee; Wen-Shiun Yueh; Chun-Lin He; Mong-Fong Lee; Lian-Tien Sun; Ching-Fong Chang (Fish Physiology and Biochemistry, 2003)